FSU immigrants in Canada: a case of positive triple selection? - Don J. DeVoretz; Michele Battisti (Institute for the Study of Labor (IZA), 2009)
This paper investigates the economic performance of immigrants from the Former Soviet Union (FSU) countries in Canada. The contribution of this paper lies in its use of a natural experiment to detect possible differential labour market performances of Soviet immigrants prior to and after the collapse of the Soviet Union. In short, the collapse of the former Soviet Union allows an exogenous supply change in the number and type of FSU immigrants potentially destined to enter Canada. For this purpose, Census microlevel data from the 1986, 1991, 1996 and 2001 Canadian Census are utilized to estimate earnings and employment outcomes for pre- and post-FSU immigrants.
urn:nbn:de:101:1-200910122515
Keywords: J61; F22; 330; Immigration; integration; Migranten; Sowjetisch; Russen; Lohn; Erwerbsverlauf; Kanada